2014
DOI: 10.1002/2014wr015852
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic watershed model for determining the effects of transient storage on nitrogen export to rivers

Abstract: Legacy anthropogenic nitrogen (N) has been suggested as a major cause for increasing riverine N exports despite significant declines in anthropogenic N inputs in many regions. However, little quantitative knowledge exists concerning the contribution of the legacy N pool to riverine N export. This study developed a dynamic watershed N delivery model to address the role of transient storage of anthropogenic N inputs on riverine N flux. Employing simple mass balance and equivalent substitution rules, the model ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 85 publications
(189 reference statements)
6
36
0
Order By: Relevance
“…Studies also demonstrated a growing N saturation responds to excessive N inputs in many highly managed watersheds Tessier and Raynal, 2003). Therefore, many N balance studies conducted in many countries and regions (Chen et al, 2014a;Drury et al, 2011;Van Meter et al, 2016;Worrall et al, 2015) suggested a very large and ongoing storage of N in terrestrial ecosystem. In terms of P, studies conducted for many watersheds across China, United States, and Europe (Chen et al, 2015b;Goyette et al, 2016;Han et al, 2012;Hong et al, 2012;Russell et al, 2008) indicated that synthetic fertilizer application and food and feed import are major sources for total anthropogenic P inputs over the past several years to decades.…”
Section: Excessive Anthropogenic Nutrient Inputsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies also demonstrated a growing N saturation responds to excessive N inputs in many highly managed watersheds Tessier and Raynal, 2003). Therefore, many N balance studies conducted in many countries and regions (Chen et al, 2014a;Drury et al, 2011;Van Meter et al, 2016;Worrall et al, 2015) suggested a very large and ongoing storage of N in terrestrial ecosystem. In terms of P, studies conducted for many watersheds across China, United States, and Europe (Chen et al, 2015b;Goyette et al, 2016;Han et al, 2012;Hong et al, 2012;Russell et al, 2008) indicated that synthetic fertilizer application and food and feed import are major sources for total anthropogenic P inputs over the past several years to decades.…”
Section: Excessive Anthropogenic Nutrient Inputsmentioning
confidence: 99%
“…The variable hydrologic and biogeochemical residence times in different landscapes along the terrestrial-aquatic continuum give rise to distinct spatial and temporal patterns of legacy nutrient pools (Chen et al, 2014a;Sharpley et al, 2013). Legacy N hot spots always occur in large watersheds with longer time for groundwater updates and areas with longer time for N biogeochemical cycling (Worrall et al, 2015).…”
Section: Distributions Of Watershed Legacy Nutrient Poolmentioning
confidence: 99%
See 3 more Smart Citations